Implementation of the Right to Visiting Service for Inmates in Class I Correctional Institution Surabaya - Kurniawan, Mohamad Fajar; Rizky, Catur; Hardyansah, Rommy; Haniyah, Haniyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The inmate visit service is very effective in contributing to reducing the crime rate and improving public safety. As a forum for coaching, protecting and guiding inmates, correctional institutions hold a great responsibility to fulfill the goals of corrections. One of them is the fulfillment of the right to visit prisoners. The purpose of this study is to find out the legal provisions and how to implement the inmate visit service in the Class I Surabaya Correctional Institution. The method used in this study is through a qualitative descriptive approach. Data was taken through interviews with visiting officers, inmates and related parties, as well as by direct observation at the Surabaya Class I Correctional Institution. In addition, analysis of documents and related literature is also used to support the findings of the research. The results of the study show that the fulfillment of the right to visit services for inmates still faces various challenges. Factors such as relatively complicated administrative requirements policies, lack of adequate facilities, as well as lack of resources. This study also found several recommendations to improve the fulfillment of the right to visit services for inmates. Measures such as the formulation of clear and firm policies, the improvement of adequate visiting facilities, and the increase of understanding and awareness of visiting officers and other related parties regarding the importance of fulfilling the rights of prisoners are needed.